DILEMA IMPLEMENTASI ASESMEN AUTENTIK PADA PENILAIAN KETERAMPILAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR (STUDI DI SD MUHAMMADIYAH BLAWONG 1 YOGYAKARTA) - Selvia Yolanda; Suwadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Skills assessment in Islamic Religious Education (PAI) at the elementary school level plays an important role in evaluating students’ competencies holistically, particularly in learning materials that require religious practices. This descriptive qualitative study, involving elementary school PAI teachers through in-depth interviews, revealed that skills assessment is implemented selectively and contextually in learning activities such as Qur’an recitation, ablution (wudhu), and prayer (shalat) by integrating psychomotor, cognitive, and affective dimensions in accordance with the principles of authentic assessment. The findings also indicate several challenges, including limited instructional time, large class sizes, diverse student abilities, and the suboptimal use of technology in the assessment process. To address these challenges, teachers employ various adaptive strategies, such as flexible time management, group-based assessment, remedial activities, parental involvement, and continuous feedback. These findings imply the need to strengthen a more standardized, integrated, and technology-based skills assessment system as a reference for teachers, schools, and policymakers in improving the quality of PAI assessment in the digital era.